2009
DOI: 10.2174/1874434600903010076
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Self-Regulation of Clinical Reasoning Skills in Nursing Students

Abstract: Aim:The purpose of this paper is to describe the research surrounding the theories and models the authors united to describe the essential components of clinical reasoning in nursing practice education. The research was conducted with nursing students in health care settings through the application of teaching and learning strategies with the Self-Regulated Learning Model (SRL) and the Outcome-Present-State-Test (OPT) Model of Reflective Clinical Reasoning. Standardized nursing languages provided the content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 24 publications
(24 reference statements)
0
29
0
7
Order By: Relevance
“…Our findings provided important evidences that can improve the learning environment in medical schools. Promoting the use of SRL strategies could not only help to improve students' academic achievements (Hosain et al, 2012;Kosnin, 2007;Pintrich, 2010) and clinical performance (Kuiper, Pesut, & Kautz, 2009) but could also help reduce the occurrence of depressive moods among medical students (Artino et al, 2011). Regarding the magnitude of the effects, the separate multivariate model indicated that all SRL subscales (except extrinsic goal orientation and peer learning) were found to be significantly negatively associated with depressionT2 when adjusted for depressionT1, anxiety, stress, and other demographic covariates.…”
Section: Psychology Health and Medicine 65mentioning
confidence: 99%
“…Our findings provided important evidences that can improve the learning environment in medical schools. Promoting the use of SRL strategies could not only help to improve students' academic achievements (Hosain et al, 2012;Kosnin, 2007;Pintrich, 2010) and clinical performance (Kuiper, Pesut, & Kautz, 2009) but could also help reduce the occurrence of depressive moods among medical students (Artino et al, 2011). Regarding the magnitude of the effects, the separate multivariate model indicated that all SRL subscales (except extrinsic goal orientation and peer learning) were found to be significantly negatively associated with depressionT2 when adjusted for depressionT1, anxiety, stress, and other demographic covariates.…”
Section: Psychology Health and Medicine 65mentioning
confidence: 99%
“…Enhancing autonomy not only increases students' engagement, but simultaneously reinforces self-regulated learning strategies and self-efficacy (Bandura, 1977;Bowers-Campbell, 2008). When students are invited to take part in peer learning through social networking they can self-monitor, selfevaluate and self-reinforce behaviours that support learning (Kuiper et al, 2009). Importantly, using social media platforms such as Facebook opens up learning by engaging with students in a way that is routine for current generations (Hamid et al, 2010;McMillan and Morrisson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los retos actuales es lograr calidad y excelencia en la formación de los recursos humanos en salud 1,2 , en la que se consideren las transformaciones suscitadas en el ámbito político, social y económico, En este sentido, los docentes gestores han realizado importantes esfuerzos para garantizar formación universitaria de calidad 3 , que incorpore los cambios en la salud de las personas y se impulse un equilibrio en los escenarios docente-asistenciales a fin de propiciar el desarrollo de modos de actuación pertinentes 4 . De igual forma, las nuevas necesidades exigen profesionales que sean creativos y resuelvan problemas cambiantes 5 , por consiguiente, es necesario que desde estudiantes aprendan a analizar y evaluar críticamente las necesidades del paciente 6 .…”
Section: Introductionunclassified